2016
DOI: 10.1093/mnras/stw2287
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the Milky Way: new insights from open clusters

Abstract: We have collected high-dispersion echelle spectra of red giant members in the twelve open clusters (OCs) and derived stellar parameters and chemical abundances for 26 species by either line equivalent widths or synthetic spectrum analyses. We confirm the lack of an age−metallicity relation for OCs but argue that such a lack of trend for OCs arise from the limited coverage in metallicity compared to that of field stars which span a wide range in metallicity and age. We confirm that the radial metallicity gradie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 104 publications
14
69
0
Order By: Relevance
“…Open clusters have been used to study Galactic chemical trends as far back as Janes (1979), where the author showed open clusters to be a reliable tracer of a Galactic radial metallicity gradient. More recently, this trend has been consistently considered a 2-function gradient (e.g., Sestito et al 2008;Bragaglia et al 2008;Friel et al 2010;Carrera & Pancino 2011;Yong et al 2012;Frinchaboy et al 2013;Reddy et al 2016;Magrini et al 2017), with the break falling between R GC ≈ 10 kpc and R GC ≈ 16 kpc. This gradient has become an important observable constraint for models of Galactic Chemical Evolution.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Open clusters have been used to study Galactic chemical trends as far back as Janes (1979), where the author showed open clusters to be a reliable tracer of a Galactic radial metallicity gradient. More recently, this trend has been consistently considered a 2-function gradient (e.g., Sestito et al 2008;Bragaglia et al 2008;Friel et al 2010;Carrera & Pancino 2011;Yong et al 2012;Frinchaboy et al 2013;Reddy et al 2016;Magrini et al 2017), with the break falling between R GC ≈ 10 kpc and R GC ≈ 16 kpc. This gradient has become an important observable constraint for models of Galactic Chemical Evolution.…”
Section: Introductionmentioning
confidence: 92%
“…Our results are consistent with Yong et al (2012) open clusters in the range 6 ≤ R GC ≤ 11 kpc, although both slopes are much shallower when they include more clusters from the literature. Carrera & Pancino (2011) and Reddy et al (2016) report [α/Fe] vs R GC gradients of 0.004 ± 0.001 dex kpc −1 and 0.014 ± 0.005 dex kpc −1 , respectively. Our results are therefore in good agreement with the literature, except perhaps for Si which appears to be almost completely flat in our case.…”
Section: The Galactic Metallicity Gradientmentioning
confidence: 99%
See 2 more Smart Citations
“…Massive (Cats. 3 and 4) stars, and more specifically their He-burning cores and, to some extent, their C-burning shells, are also predicted to be s-nuclide producers through the operation of the 22 Ne (α , n) 25 Mg . This neutron source can indeed be active in these locations that are hotter than the He shell of AGB stars.…”
Section: Specific S-process Sitesmentioning
confidence: 99%